I’LLAH HADIST; POSISI DAN PENGARUHNYA TERHADAP KESHAHIHAN HADIST - Rafi'atun Najah Qomariah; Rafi'atun Najah Qomariah (Tarbawi, 2021)
The study of 'illah hadits is very important because it determines whether a hadits is truly authentic or not. This research aims to delve into the concept of 'illah hadits, its position in hadits criticism, and its impact on the authenticity of hadits. This study uses a qualitative approach and a literature review process. The results of this research show that the concept of 'illah hadits is key to hadits criticism and provides insights into the historical background, events, and contexts that influence the validity of hadits. 'Illah is the hidden defect in its authentic hadits. The 'illah of hadits is located in the chain of transmission of the hadits narrated by Ya'la bin 'Ubaid and the text of the hadits narrated by Ibrahim ibn Thahman, such as the hadits narrated by Baqiyyah from Yunus. The steps to determine the "illah" in a hadits involve a deep understanding of the hadits, textual studies, historical context, the study of Asbab al-Wurud, examination of the narrators, and hadits methodology. The process involves philological analysis, understanding of historical context, identification of causes, examination of hadits transmitters, and hadits methodology. Through these steps, a comprehensive and scientific understanding of "illah" in hadits is achieved.